APPLICATION OF THE RUSLE MODEL TO CALCULATE SOIL WATER EROSION IN THE LOWER BASIN OF THE VIRÚ RIVER, LA LIBERTAD REGION, 2022 (LACCEI, 2024)
Soil degradation is a serious threat to agroecosystems and landscapes in many countries. These processes are much more intensified in high-intensity episodic rains over cultivated areas. The need to estimate soil loss in a variety of spatial and temporal scales has been recognized, therefore, due to the difficulty it presents for the control of soil loss due to water erosion, as an alternative to a mathematical method is developed, being Thus, the objective of this research work, application of the RUSLE model to calculate soil water erosion, obtaining an average erosion of 57.14 T.ha-1.Year-1 in the lower basin of the Virú river, La Libertad Region, 2022, which discharged into the Pacific Ocean.